Rancangan Sistem Monitoring Greenhouse Hidroponik Berbasis IoT - Hersydano, Muhammad Rayhan; Pamungkas, Syahdam Gibran; Putra, I Gusti Lanang Dwitya; Rahman, Abdul; Warohma, Ayu Mawadda (MDP Student Conference, 2025)
Hydroponic methods are becoming increasingly popular as a modern agricultural solution, especially in urban areas with limited land. However, maintaining optimal environmental conditions is a major challenge in hydroponic systems. This study designs an Internet of Things (IoT)-based greenhouse monitoring system to improve the efficiency of plant monitoring and management. The system uses ESP32 microcontroller as the main controller, integrated with a DS18B20 sensor for temperature, a pH sensor, a TDS sensor for nutrient concentration, and a floater sensor to measure water level. Sensor data is transmitted in real-time via a WiFi network to a web-based monitoring platform, enabling more practical and accurate remote monitoring. The results indicate that this system can provide accurate information about plant environmental conditions and support automation in nutrient management and irrigation. Thus, this system offers an innovative solution for more efficient, controlled, and technology-based hydroponic farming.